Manual dietetic practice - Gandy, Joan (Wiley, 2014)
Since publication of its first edition, Manual of Dietetic Practice has remained an essential guide to the key principles of dietetics and a core text for healthcare professionals looking to develop their expertise and specialist skills. Published on behalf of the British Dietetic Association, the UK professional body for dietitians, it covers the entire dietetics curriculum and is also an ideal reference text for qualified practitioners. The book has been extensively restructured for its fifth edition and is now divided into two parts to make it easier to locate key topics